Three short stories from "The Captain" volume XXVII : How Dymock Came to Derry; Jack Devereux's Scoop; The Powder Hulk - Westerman, Percy F. (Percy Francis), 1876-1959; Hodgson, E. S. (Edward Smith), 1866-1937; Soper, George, 1870-1942 (Salt Lake City, UT : Project Gutenberg, 2018)
"Three short stories from 'The Captain' volume XXVII" by Percy F. Westerman is a collection of adventure tales written in the early 20th century. The stories are set against historical backdrops and focus on themes of bravery and camaraderie in the face of danger. The collection includes three distinct narratives: "How Dymock Came to Derry," "Jack Devereux's Scoop," and "The Powder Hulk," showcasing young protagonists who rise to the occasion during perilous situations. In "How Dymock Came to Derry," the story follows Jock Dymock, a young man tasked with delivering a critical message to the besieged city of Londonderry amidst conflict in the late 17th century. His daring swim through treacherous waters leads to a crucial delivery of provisions to the starving defenders. "Jack Devereux's Scoop" features a young war correspondent in Morocco who navigates a chaotic battlefield, grappling with circumstances of war and competition in the journalism field. Lastly, "The Powder Hulk" depicts two boys and their brave effort to thwart a criminal act targeting a hulk storing explosives, highlighting their resourcefulness in a tense situation. Each story emphasizes adventure, courage, and the spirit of youth in the face of adversity. (This is an automatically generated summary.)
Release date is 2018-07-18
Produced by R.G.P.M. van Giesen
Keywords: Short stories; Adventure stories